Analisis Nilai Perusahaan Food & Beverage di Bursa Efek Indonesia - Karim, Alvian Nur Karim; Nur, Dhani Ichsanuddin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The objective of this research is to examine the variables affecting the stock value of food and beverage firms listed on the Indonesian Stock Exchange (IDX). This research examines a number of variables, including firm value as the dependent variable, profitability as an independent variable, and liquidity as an independent variable. The Food and Beverage Sub-Sector's Manufacturing Industry Consumption Goods Factory Zone, which includes 33 industries, serves as the study's population. Purposive sampling, which is the collecting of samples with aims and intents in categorizing drawings based on specified criteria, was used to choose the sample for this study. 25 manufacturing sectors from the food and beverage sub-zone of the consumer goods firm zone served as the samples. The study's findings indicate that although profitability and liquidity may both increase a business's value, company expansion cannot. These findings are particularly relevant to the food and beverage firms listed on the Indone Keywords : company growth, profitability, liquidity, company value.